Percepcja barier rozwoju elektromobilności w kontekście postaw ekologicznych mieszkańców województwa podkarpackiego - Kud, Krzysztof (Polityka i Społeczeństwo, 2020)
The transport needs of the population are constantly growing, and the consequences of car transport, fueled by gasoline and diesel engines, constitute a growing ecological problem. Electromobility is a direction that is currently indicated as a solution to these problems, especially in large cities suffering from poor air quality. New technological solutions often encounter many barriers, and usually the main barrier is the mental barrier. The study analyzes the perception of barriers to the development of electromobility by the inhabitants of the Podkarpackie Voivodeship. The study aims to verify the hypothesis about the dependence of the perception of electromobility on the ecological attitude of the inhabitant. It has been assumed throughout the present study that the assessment of activity regarding waste segregation, relation to animals, etc. is an expression of an ecological attitude, and the attitude towards electromobility depends on it.